2010
DOI: 10.1111/j.1365-2621.2010.02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Wine industry residue as antioxidant in cooked chicken meat

Abstract: The effectiveness of grape extracts as food ingredient has been tested in various systems. The objective of this study was to evaluate the efficiency of four concentrations of residues of the wine industry in delaying lipid oxidation in processed chicken meat stored under refrigeration. The development of oxidation during the 14-day storage was evaluated through the thiobarbituric acid reactive substances method (TBAS). The analyses of phenolic compounds and antioxidant activity were performed in grape residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…The samples including 10 % GSP had TBARS levels lower than 40 % when compared to the control during 5 months frozen storage. These results were in agreement with Rababah et al (2006) and (Shirahigue et al 2010), who found a reduction in TBARS in chicken meat with GSE during refrigerated storage. Recently many storage experiments were carried out to prove the antioxidative effects of plant materials and some of them investigated a considerable reduction in TBARS during the first part of the storage period.…”
Section: Changes In Povs During Frozen Storage Of Precooked Chicken Nsupporting
confidence: 92%
“…The samples including 10 % GSP had TBARS levels lower than 40 % when compared to the control during 5 months frozen storage. These results were in agreement with Rababah et al (2006) and (Shirahigue et al 2010), who found a reduction in TBARS in chicken meat with GSE during refrigerated storage. Recently many storage experiments were carried out to prove the antioxidative effects of plant materials and some of them investigated a considerable reduction in TBARS during the first part of the storage period.…”
Section: Changes In Povs During Frozen Storage Of Precooked Chicken Nsupporting
confidence: 92%
“…Extraction was carried out as described by Shirahigue et al (2010) with a few modifications (schematic representation shown in Fig. 1).…”
Section: Preparation Of the Grape Pomace Extracts (Gpe)mentioning
confidence: 99%
“…A positive correlation was reported between the antioxidant activity and the total phenolic compounds in grape byproducts (Alonso et al 2002). For example, grape seed extract and other plant extracts have been shown to have an antioxidative effect on beef (Ahn et al 2002), turkey (Mielnick et al 2006), fish muscle (Sanchez-Alonso and Borderias 2008) and chicken meat (Shirahigue et al 2010). For example, grape seed extract and other plant extracts have been shown to have an antioxidative effect on beef (Ahn et al 2002), turkey (Mielnick et al 2006), fish muscle (Sanchez-Alonso and Borderias 2008) and chicken meat (Shirahigue et al 2010).…”
Section: Introductionmentioning
confidence: 98%